The Long-Lasting Effects of Family and Childhood on Adult Wellbeing: Evidence from British Cohort Data - Sarah Flèche; Warn N. Lekfuangfu; Andrew E. Clark (Global Labor Organization (GLO), 2018)
To what extent do childhood experiences continue to affect adult wellbeing over the life course? Previous work on this link has been carried out either at one particular adult age or for some average over adulthood. We here use two British birth-cohort datasets (the 1958 NCDS and the 1970 BCS) to map out the time profile of the effect of childhood experiences on adult outcomes, including life satisfaction. We find that the effects of many aspects of childhood do not fade away over time but are rather remarkably stable. In both birth-cohorts, child non-cognitive skills are the strongest predictors of adult life satisfaction at all ages. Of these, emotional health is the strongest. Childhood cognitive performance is more important than good conduct in explaining adult life satisfaction in the earlier NCDS cohort, whereas this ranking is inverted in the more recent BCS.
Keywords: A12; D60; I31; 330; life satisfaction; cohort data; childhood; adult outcomes